Potential Biomarkers of the Earliest Clinical Stages of Parkinson’s Disease - Anelya Kh. Alieva; Elena V. Filatova; Aleksey V. Karabanov; Sergey N. Illarioshkin; Petr A. Slominsky; Maria I. Shadrina (Parkinson's Disease)
Parkinson’s disease (PD) is a widespread neurodegenerative disorder. Despite the intensive studies of this pathology, in general, the picture of the etiopathogenesis has still not been clarified fully. To understand better the mechanisms underlying the pathogenesis of PD, we analyzed the expression of 10 genes in the peripheral blood of treated and untreated patients with PD. 35 untreated patients with PD and 12 treated patients with Parkinson’s disease (Hoehn and Yahr scores 1-2) were studied. An analysis of the mRNA levels of ATP13A2, PARK2, PARK7, PINK1, LRRK2, SNCA, ALDH1A1, PDHB, PPARGC1A, and ZNF746 genes in the peripheral blood of patients was carried out using reverse transcription followed by real-time PCR. A statistically significant and specific increase by more than 1.5-fold in the expression of the ATP13A2, PARK7, and ZNF746 genes was observed in patients with PD. Based on these results, it can be suggested that the upregulation of the mRNA levels of ATP13A2, PARK7, and ZNF746 in untreated patients in the earliest clinical stages can also be observed in the preclinical stages of PD, and that these genes can be considered as potential biomarkers of the preclinical stage of PD.